The Politics of Memory and History: Re-Imagining Postmodern India through Salman Rushdie’s Historical Fiction - Joshi, Rekha; Pant, Kavita (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Postmodernism in Indian English literature has emerged as a critical lens for understanding the complexities of history, identity and cultural transformation in contemporary India. Characterized by its skepticism toward metanarratives, its embrace of fragmentation and its interrogation of memory, postmodernism provides a fertile ground for re-examining the narratives of nationhood and collective belonging. Among Indian English writers, Salman Rushdie has played a decisive role in reshaping the literary and cultural imagination through his innovative use of historiographic metafiction, satire and magical realism. Although Rushdie’s works have extensively discussed in relation to diaspora, hybridity and postcolonial identity, there remains a notable gap in scholarship concerning his sustained engagement with the politics of memory and the revision of historical narratives in the context of postmodern India. This study addresses that gap by analyzing how Rushdie’s historical novels particularly Midnight’s Children, Shame, The Moor’s Last Sigh and The Enchantress of Florence intervene in the contested terrain of collective memory and history. The methodology combines close textual analysis with cultural theory and postmodern historiography, situating Rushdie’s fiction within broader debates on memory, nationhood and identity. The findings suggest that Rushdie deliberately disrupts linear history, foregrounds fragmented memory and reconfigures India’s modernity through postmodern fictional strategies. By advancing the conceptual framework of “memory–history dialectics”, the paper contributes to Indian English literary studies by demonstrating how Rushdie’s novels transform the politics of remembering and forgetting into a site of resistance, thereby redefining the contours of postmodern Indian identity.